Synthesis, X-ray structure, in silico calculation, and carbonic anhydrase inhibitory properties of benzylimidazole metal complexes - Mehdi Bouchouit; Sofiane Bouacida; Bachir Zouchoune; Hocine Merazig; Silvia Bua; Zouhair Bouaziz; Marc Le Borgne; Claudiu T. Supuran; Abdelmalek Bouraiou (Taylor & Francis Group, 2018)
Three coordination compounds of formula {M(bmim)2Cl2} were synthetised (M = Co, Zn, and Hg) and fully characterised. Each complex incorporates 1-benzyl-2-methylimidazole (bmim) as ligand. The coordination polyhedron around the metal center for all complexes has a quasi-regular tetragonal geometry. Density functional theory calculations were carried out on the title compounds and as well on hypothetical complexes (Cu, Ni), in order to elucidate their electronic and molecular structure. The calculations reproduced the Co, Zn, and Hg experimental structures and could predict stable complexes in the case of Ni(II) and Cu(II) ions. The carbonic anhydrase (CA, EC 4.2.1.1) inhibitory effects of the three complexes were investigated. Only compound {Hg(bmim)2Cl2} (3) exhibited a modest inhibitory effect against hCA I, probably due to the affinity of Hg(II) for His residues at the entrance of the active site cavity.